The Essence of Islamic Religious Education Curriculum: Integrating Islamic Values with Contemporary Education - Faruq, Asrul; Raharjo, Raharjo; Sholeh, Nur (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
The purpose of writing this article is to explain the essence of the Islamic religious education curriculum in schools. Where the Islamic education curriculum plays a central role in shaping identity and scientific development in the context of religion-based education. This research is literature research by examining the nature of the Islamic education curriculum. The literature review method includes indirect observation or looking at internet platforms, books and other sources, then analyzing facts relevant to the specified topic. The essence of the Islamic education curriculum is activities that involve learning plans, material content and student learning method strategies that are implemented well, which will create a generation that is obedient and obedient to Allah SWT, has a high religious attitude, becomes human beings who are highly capable, have interests and appropriate talent.